Birth order and health of newborns: What can we learn from Danish registry data? - Anne Ardila Brenøe; Ramona Molitor (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2015)
Research has shown a strong negative correlation between birth order and cognitive test scores, IQ, and educational outcomes. We ask whether birth order differences in health are present at birth using matched administrative data for more than 1,000,000 children born in Denmark between 1981 and 2010. Using family fixed effects models, we find a positive and robust birth order effect; lower parity children are less healthy at birth. Looking at the potential mechanisms, we find that during earlier pregnancies women have higher labor market attachment, behave more risky in terms of smoking, receive more prenatal care, and are diagnosed with more medical pregnancy complications. Yet, none of these factors explain the birth order differences at birth. This positive birth order effect at birth stands in stark contrast to a negative birth order effect in educational performance. Once we control for health at birth, the negative birth order effect in educational performance further increases.
Keywords: I10; I12; J12; J13; 330; birth order; parity; child health; fetal health; health at birth; education